Pediatric Critical Care Medicine Training in India: Past, Present, and Future - Bhalala, Utpal; Khilnani, Praveen (Frontiers in Pediatrics, 2018)
Pediatric critical care services in India have grown with leaps and bounds. There has been a growing need of physicians specially trained in pediatric critical care medicine in India. Physicians returning to India after their formal training in pediatric critical care medicine abroad have partly supported this growing need. Development of formal pediatric critical care medicine training programs in India has been a huge step towards supporting the growing clinical needs. This article focuses on advances in pediatric critical care training in India and its future directions.